2022
DOI: 10.1093/ofid/ofac462
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated With Antigen Test Positivity Following SARS-CoV-2 Infection Among Health Care Workers in Los Angeles

Abstract: Surges of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections among health care workers (HCWs) have led to critical staffing shortages. From January 4 to February 4, 2022, we implemented a return-to-work antigen testing program for HCWs, and 870 HCWs participated. Antigen test positivity was 60.5% for those ≤5 days from symptom onset or positive polymerase chain reaction (PCR), and 47.4% were positive at day 7. Antigen positivity was associated with receiving a booster vaccination and being… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated RAT positivity rates of 31%-58% after at least 5 days of isolation [3], suggesting a strategy based on a negative RAT and symptom resolution to reduce the number of individuals leaving isolation while still infectious as well as reducing the number of people who remain unnecessarily in isolation [6,7]. A study of a health care worker's return-to-work antigen testing program found that antigen test positivity was 60.5% at day 5 and 47.4% positive at day 7 [8]. A second study of college athletes found that after 7 days of isolation, 27% continued to test positive on rapid antigen tests; it concluded that a 5-day isolation period may be insufficient [9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated RAT positivity rates of 31%-58% after at least 5 days of isolation [3], suggesting a strategy based on a negative RAT and symptom resolution to reduce the number of individuals leaving isolation while still infectious as well as reducing the number of people who remain unnecessarily in isolation [6,7]. A study of a health care worker's return-to-work antigen testing program found that antigen test positivity was 60.5% at day 5 and 47.4% positive at day 7 [8]. A second study of college athletes found that after 7 days of isolation, 27% continued to test positive on rapid antigen tests; it concluded that a 5-day isolation period may be insufficient [9].…”
Section: Introductionmentioning
confidence: 99%